Development of an in vitro model of the dentogingival junction using 3D organotypic constructs. (3rd October 2020) - Lu, Emily Ming‐Chieh; Hobbs, Carl; Ghuman, Mandeep; Hughes, Francis J.
Abstract: Objectives: The overall aim was to propose a plausible model of the dentogingival junction (DGJ) to deepen our understanding of the extrinsic influences responsible for the development of the junctional epithelial phenotype. The specific objective was to test the hypothesis that epithelial migration and proliferation would be inhibited by periodontal ligament (PDL) fibroblasts in an in vitro model of the DGJ consisting of 3D organotypic cultures. Background: Previously, we showed that 3D organotypic cultures containing human gingival fibroblasts (HGF) supported the development of a multi‐layered epithelium, while constructs containing human periodontal ligament fibroblasts (HPDLF) resulted in epithelial atrophy (Lu EMC, Hobbs C, Dyer CJ, Ghuman M, Hughes FJ. J Perio Res ., 2020). However, changes in epithelial phenotype have not been studied within an in vitro model of the DGJ. Methods: The in vitro model of the DGJ comprised of a donor HGF construct (H400 epithelium overlying HGF‐collagen matrix) supported by a dimensionally larger recipient collagen bed enriched with HPDLF. Samples were harvested, fixed and processed for immunohistochemistry. The changes in epithelial migration and proliferation following contact with HPDLF were assessed by measuring the horizontal extension of the epithelial outgrowth on the recipient collagen matrix. Results: Within our in vitro model of the DGJ, epithelial migration and proliferation were inhibited following contact with the recipient HPDLF. By contrast, the control set‐up showed a relative increase in epithelial growth, where the epithelium came into contact with the recipient HGF. Overall, there were limited changes in the molecular expression of keratin markers. Conclusion: This study has proposed a plausible in vitro model of the DGJ to illustrate the role of different fibroblasts in the regulation of dentogingival epithelia. Furthermore, it suggests that the anatomical positional stability of the JE and its apparent resistance to apical migration could be associated with its interaction with the PDL.